Ketika Anak Bertanya dan Berefleksi: Benih-Benih Penerapan Deep Learning di Kelas PAUD - Rochmi Hastuti; Raden Roro Vemmi Kesuma Dewi; Thoriquddin (Khidmatussifa: Journal of Islamic Studies, 2025)
The ability of young children to ask questions and reflect on their learning experiences serves as an early indicator of deep learning processes. This study aims to explore the types of questions and reflections that naturally emerge in early childhood classrooms and to identify the teacher's role in facilitating these processes as seeds of deep learning implementation. The research was conducted at PAUD Kunang-Kunang, located in Cipanas District, Cianjur Regency, using a descriptive qualitative approach. Data were collected through participatory observation and in-depth interviews with the classroom teacher. The findings reveal that children are capable of posing reflective questions related to their personal experiences and demonstrate an emerging awareness of their learning processes. Teachers actively encourage open-ended questioning, provide space for exploration, and respond constructively to children's reflections. These results indicate that in the PAUD context, there are promising signs or seeds of deep learning practices that can be further cultivated through responsive, reflective, and meaningful learning design.